(untitled) - Tomsovic, Steven (Singapore, 1998)
Includes bibliographical references; In this volume, the articles include: (i) tunneling out of a metastable state, (ii) coherence between two wells in tunneling contact, (iii) the consequences of the nature of the underlying dynamics (i.e. regular motion, chaos or some mixture) in low-dimensional systems and its connection to newly identified tunneling phenomena such as chaos-assisted tunneling, (iv) nanomagnetic systems with focus on comparing environmental descriptions of nuclear spins and oscillators, (v) solitons in Bose condensates, (vi) tunneling out of the nuclear superdeformed well and its use as a probe of pairing and chaos in excited nuclear states, and (vii) problems linked to the Bose condensed phase of atomic alkali gases.
Keywords: Nuclear magnetism -- Congresses; Nuclear spin -- Congresses; Tunneling (Physics) -- Congresses; Từ tính hạt nhân -- Kỷ yếu; Spin hạt nhân -- Kỷ yếu